TERRITORY AS A CAGE: HETERONOMY, ACCUMULATION BY DISPOSSESSION, AND THE MIRAGE OF AUTONOMY IN BRAZILIAN SOCIO-SPATIAL FORMATION - Luís André, André (Revista Gênero e Interdisciplinaridade, 2026)
This text proposes a critical reflection on the concept of territory, radically distinguishing it from the notions of space and place. Based on a periodization of Brazilian socio-spatial formation, colonial, agro-export, national-developmentalist, and contemporary, it argues that territory fundamentally constitutes a device of heteronomy, that is, a space of instituted power produced through pacts among dominant classes, the State, and corporations, whose primary function lies in control, confinement, and accumulation by dispossession. Unlike place, understood as a space saturated with affections, memories, and everyday life experiences, territory imposes itself as a besieged space, frequently experienced by subaltern groups as a form of condemnation. The text criticizes romanticized perspectives that confuse defensive resistance with autonomy, warning against the risk of what is termed “geographical Stockholm syndrome.” Drawing upon the theoretical contributions of Henri Lefebvre, Claude Raffestin, Hakim Bey, Noam Chomsky, and Marcelo Lopes de Souza, it argues that autonomy does not emerge spontaneously from the everyday use of territory, but rather requires a conscious political project, horizontal organization, and a rupture with the logic of capital and the State. Defensive territorialities are understood as legitimate and necessary, yet insufficient for emancipation. The text concludes that critical geography must adopt a libertarian perspective grounded in concrete practice rather than idealizations, maintaining the horizon of autonomy as a historical imperative, even though every autonomous experience remains temporary and permanently threatened by the “territorial gangsterism” of hegemonic powers.